Student Perceptions of the Athletic Therapy Interactive Concussion Educational (AT-ICE) Tool - King, Colin D.; Hynes, Loriann M. (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
Previous research has identified a considerable amount of variability in how healthcare professionals are taught to recognize, assess, and manage concussions. Responding to these findings, an innovative applied learning technology tool, the Athletic Therapy Interactive Concussion Educational (AT-ICE) Tool, was developed to help teach athletic therapy students how to recognize, assess, and manage concussions. The purpose of this research was to employ an interpretivist conceptual framework to explore athletic therapy students’ perceptions of this tool. A questionnaire was used to identify individual factors that impacted student perceptions of AT-ICE and how it could be integrated into the classroom. Overall, participants enjoyed using AT-ICE and felt it helped to stimulate their critical thinking about the entire continuum of concussion care. Several important themes emerged including the importance of detailed scenarios, sharing lived experiences, and integrating anatomy within assessment and management scenarios. Findings suggest that AT-ICE was an effective educational technology that stimulated critical thought throughout the entire continuum of concussion care. Future research could continue to investigate the effectiveness of the tool or explore different ways to implement it in formal athletic therapy educational settings.